2017
DOI: 10.1002/adma.201704412
|View full text |Cite
|
Sign up to set email alerts
|

Number‐Resolved Single‐Photon Detection with Ultralow Noise van der Waals Hybrid

Abstract: Van der Waals hybrids of graphene and transition metal dichalcogenides exhibit an extremely large response to optical excitation, yet counting of photons with single-photon resolution is not achieved. Here, a dual-gated bilayer graphene (BLG) and molybdenum disulphide (MoS ) hybrid are demonstrated, where opening a band gap in the BLG allows extremely low channel (receiver) noise and large optical gain (≈10 ) simultaneously. The resulting device is capable of unambiguous determination of the Poissonian emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 33 publications
0
41
0
Order By: Relevance
“…This corresponds to a detectivity of assuming a active area. Currently, such performance has been approached in graphene-based detectors operating at low temperature (T ∼ 100 K) [ 101 ]. Atomically-thin single-photon detectors, operating at room temperature, will allow a much faster integration into electronics and computation systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This corresponds to a detectivity of assuming a active area. Currently, such performance has been approached in graphene-based detectors operating at low temperature (T ∼ 100 K) [ 101 ]. Atomically-thin single-photon detectors, operating at room temperature, will allow a much faster integration into electronics and computation systems.…”
Section: Discussionmentioning
confidence: 99%
“…Using this structure, the authors demonstrated a multilevel optoelectronic memory using light and gate pulses to write and erase each bit, respectively ( Figure 7 b). In a follow up work, they replaced monolayer graphene with bilayer and, by dual gating, they electrostatically opened a band gap of ∼ [ 101 ], which resulted in a reduction in the channel noise by 6 to 8 orders of magnitude. This allowed them to demonstrate a number-resolved photo counter capable of determining the Poissonian emission statistic of an LED ( Figure 7 c).…”
Section: Hybrid and Heterostructure Photodetectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above result, i.e., effective temperature increasing with increasing photon energy, is promising for microwave photon detection. Indeed, with further optimization of microwave coupling structure, for example through utilization of a meander line 25 , quarter wave resonator 4 , or log periodic antennas 26 , measurements can be done at much lower microwave power level, which may provide more support for single photon detection with number resolving 9 , 27 capability. Compared to other superconducting photon detectors, such as transition edge sensors (TESs), the photon detection in this device is done by the zero-bias resistance, thus avoiding a large source-drain current needed, for example, in a TES structure 28 .…”
Section: Resultsmentioning
confidence: 99%
“…In most quantum communication schemes [4][5][6][7][8][9], the expensive critical element is the photon detector, which largely determines the quantum signal utilization, signal to noise ratio, cost and reliability of the system, as well as its main functionality and complexity of maintenance during operation. Currently, to ensure high quantum communication (QC) devices performance, two main types of quantum detectors are widely used: single-photon avalanche detector (SPAD) [10,11] and high-efficiency superconducting single-photon detector (SSPD) [12][13][14][15][16]. Promising results for stable urban quantum networks and longdistance QCs have been recently obtained with SPAD and SSPD detectors.…”
Section: Intercity Quantum Networkmentioning
confidence: 99%